The Exclusive Brethren in Scotland: A Historical Overview, 1838-2018 - Dickson, Neil T. R. (The journal of CESNUR, 2021)
After a slow beginning, the Exclusive Brethren in Scotland were established by mid-Victorian revivalism, and continued to grow into the early twentieth century. Thereafter, numbers remained stable, with some moderate growth, while there was an increasing introversion that directed attention away from society to internal concerns. The leadership of James Taylor Jr. proved a decisive turning point when the connexion divided over his imposition of rules, culminating in disintegration after allegations over his conduct in Aberdeen in 1970. At present, they have recovered in Scotland to a modest degree while maintaining and reinforcing their separatism.